2005
DOI: 10.3354/meps297169
|View full text |Cite
|
Sign up to set email alerts
|

Amino acid exposure modulates the bioactivity of biofilms for larval settlement of Hydroides elegans by altering bacterial community components

Abstract: Possible relationships among amino acids, bacterial community structure (in terms of relative abundance of bacterial species) of marine biofilms, and larval settlement of Hydroides elegans were investigated. Two day old biofilms were first exposed to 8 different amino acids for 24 h. The bacterial abundance on the treated biofilms was then determined by epi-fluorescence microscopy, and the bacterial community profile was revealed through T-RFLP (terminal restriction fragment length polymorphism) analysis of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 32 publications
1
11
0
Order By: Relevance
“…For example, naturally occurring polar peptides isolated from crude extracts of adult polychaetes (H. elegans) and bryozoans (B. neritina) were able to induce settlement in corresponding larvae . Also, amino acids of natural and synthetic origin have been analyzed for their ability to induce settlement of larvae of oysters (Zimmer-Faust and Tamburri, 1994), polychaetes (Beckmann et al, 1999;Jin and Qian, 2005;Zimmer-Faust and Tamburri, 1994) and barnacles (Mishra and Kitamura, 2000). Moreover, protein molecules of natural origin containing carbohydrate moieties also have been known to induce settlement of marine larvae (Dreanno et al, 2006;Larman et al, 1982).…”
Section: Discussionmentioning
confidence: 99%
“…For example, naturally occurring polar peptides isolated from crude extracts of adult polychaetes (H. elegans) and bryozoans (B. neritina) were able to induce settlement in corresponding larvae . Also, amino acids of natural and synthetic origin have been analyzed for their ability to induce settlement of larvae of oysters (Zimmer-Faust and Tamburri, 1994), polychaetes (Beckmann et al, 1999;Jin and Qian, 2005;Zimmer-Faust and Tamburri, 1994) and barnacles (Mishra and Kitamura, 2000). Moreover, protein molecules of natural origin containing carbohydrate moieties also have been known to induce settlement of marine larvae (Dreanno et al, 2006;Larman et al, 1982).…”
Section: Discussionmentioning
confidence: 99%
“…For example, Lau et al (2003) demonstrated that settlement of larval Polychaetes was shown to be affected by extracellular polymers (EPS) from bacteria from the Rhodobacteraceae. Understanding the dynamics of primary bacterial settlers is particularly important because these changes may play a role in the succession and settlement of some invertebrate species onto artificial surfaces (Kirchman et al, 1982;Lau et al, 2002Lau et al, , 2005Lee & Qian, 2003;Qian et al, 2003;Webster et al, 2004;Jin & Qian, 2005). The same bacteria on different substrates and in different combinations may have different effects on larva settlement (Kavouras & Maki, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that in the marine environment, seasonal changes affect the chemical composition of the conditioning film, and that these changes affect the initial adhering community composition (Bakker et al, 2003;Bhosle et al, 2005). Indeed invertebrate larval settlement has been suggested to be a function of the biofilm community's bacterial species composition (Kirchman et al, 1982;Lau et al, 2002Lau et al, , 2005Lee & Qian, 2003;Webster et al, 2004;Jin & Qian, 2005). Indeed invertebrate larval settlement has been suggested to be a function of the biofilm community's bacterial species composition (Kirchman et al, 1982;Lau et al, 2002Lau et al, , 2005Lee & Qian, 2003;Webster et al, 2004;Jin & Qian, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…To date, the isolated bacterial strains that induce settlement of H. elegans , as well as the environmental biofilms that have been the subject of settlement assays, have come from bays and harbours where the tubeworm resides (e.g. Hawai‘i, Unabia and Hadfield, ; Hong Kong, Jin and Qian, ; India, Arumugam, ; California, Shikuma et al ., ). This leaves the significant question: are the bacteria that induce settlement uniquely present in these harbour biofilms compared to biofilms from locations not known to harbour dense populations of H. elegans ?…”
Section: Introductionmentioning
confidence: 99%